A study of the reasons for irregular dental attendance in a private dental college in a rural setup - George Anoj; Hoshing Abhijeet; Joshi Nilesh (Wolters Kluwer Medknow Publications, 2007)
The mouth is regarded as a mirror and the gateway to health. Integration is required between the dental practitioner and the patient, if good dental health is to be attained. Various treatment modalities of late frequently require appointments, which are more than one in number for completion of the entire treatment program. This study was taken up to determine the impact of reported dental attendance patterns of patients on the oral health and treatment quality in teaching hospitals and also on the quality of life in rural areas. Aims and Objectives: 1. To assess the reasons for irregular dental care in the patients attending the clinics in teaching hospitals. 2. To assess the satisfaction of the patient as regards the treatment rendered in the teaching institutes. 3. To correlate the gender of the patient with the regularity in the recall attendance. Materials and Methods: A hospital-based cross-sectional study was conducted using a systematic random sampling method, and every alternate subject was selected from the patients attending the OPD of Department of Periodontics and Community Dentistry. The data was collected using the interview method with the help of a structured, pretested questionnaire. Results and Conclusion: Out of 288 patients, 94 failed to attend the recall appointments. In these 94 patients, various reasons for not attending recall were assessed, and lack of time was found to be the most common reason for non-attendance. Relationship between age and reasons for not reporting was found to be significant ( P < 0.01). Patient satisfaction survey showed that 51.54% of the patients were satisfied with the dental treatment rendered. The present study also showed that males are more prompt in attending recall appointments as compared to females. A positive and significant correlation between literacy and patient reporting status was found ( P < 0.01).